2016
DOI: 10.1016/j.eururo.2016.01.034
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Mapping Study Using Fluorescence Sentinel Lymph Node Detection in Patients with Intermediate- and High-risk Prostate Cancer Undergoing Extended Pelvic Lymph Node Dissection

Abstract: There is controversy about how extensive lymph node dissection (LND) should be during prostatectomy. We investigated the lymphatic drainage of the prostate and whether sentinel node fluorescence techniques would be useful to detect node metastases. We found that the drainage pattern is complex and that the sentinel node technique is not able to replace extended pelvic LND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 10 publications
6
50
0
1
Order By: Relevance
“…These findings support our LN mapping studies [6,16], speaking against the echelon theory that postulates that metastases do not occur in LNs of the second (common iliac vessels) or third echelon (paraaortal/paracaval) as long as the first echelon (areas caudal to the common iliac bifurcation) is free of tumour. In addition, over a century ago Cun eo and Marcille described three main paths draining the prostate [17]: lymphatics stretched along the external iliac vessels, internal iliac vessels and common iliac vessels.…”
Section: Discussionsupporting
confidence: 88%
“…These findings support our LN mapping studies [6,16], speaking against the echelon theory that postulates that metastases do not occur in LNs of the second (common iliac vessels) or third echelon (paraaortal/paracaval) as long as the first echelon (areas caudal to the common iliac bifurcation) is free of tumour. In addition, over a century ago Cun eo and Marcille described three main paths draining the prostate [17]: lymphatics stretched along the external iliac vessels, internal iliac vessels and common iliac vessels.…”
Section: Discussionsupporting
confidence: 88%
“…Conventional imaging techniques are inadequate for LN staging in PCa. MRI, CT, positron emission tomography (PET)/CT and fluorescence sentinel lymph node detection are neither sensitive nor specific enough to reliably detect LN metastases before RP . Recent data on the novel PET tracer agent Glu‐NH‐CO‐NH‐Lys‐(Ahx)‐[68Ga(HBED‐CC)](PSMA) has shown promising sensitivity (33–85%) and specificity (82–100%) for both the detection of PCa recurrence and LN metastases .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to staging, ePLND may also be curative, or at least beneficial, in a subset of patients with limited LN metastases [4,5]. metastases before RP [6][7][8][9]. Recent data on the novel PET tracer agent Glu-NH-CO-NH-Lys-(Ahx)-[68Ga(HBED-CC)] (PSMA) has shown promising sensitivity (33-85%) and specificity (82-100%) for both the detection of PCa recurrence and LN metastases [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Also, carbon NP suspension injection approved for LN mapping is extensively used by surgeons and researchers. [62,63] Many clinical trials have shown favorable results of intraoperative SLN detection with ICG, [64][65][66] even in robotassisted laparoscopic surgery. Radionuclide-labeled NMs for LN tracers have high sensitivity, but they are limited by the difficulty in distinguishing SLNs from other DLNs and radiation exposure to patients and doctors.…”
Section: Mapping Sentinel Lymph Nodes (Slns) For Surgerymentioning
confidence: 99%